New storage facilities for CIAT's germplasm - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The Genetic Resources Unit (GRU) of the Centro Internacional de Agricultura Tropical (CIAT) recently completed the construction of new facilities for storing bean, cassava and tropical pasture germplasm. The facilities comprise a cold room (-20C),...